Peculiarities of Scientific Communication in the Frame of International Ecological Integration - Ларіна, О. С.; Суховецька, С. В.; Шелест, З. М. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2014)
Peculiarities of scientific-technical interpreting as a part of communication in the frame of international ecological integration are analyzed. The Ukrainian scientific and technical texts on comparison with the English texts are characterized by a greater degree to depersonalized. The manner of exposition is characterized by predominance of combinations, by the kernel of which a noun serves. In scientific style of Ukrainian homogeneous members, participating and adverbial participial turns, are widely used.